Th17 Cell-Associated Response to Borrelia Burgdorferi Outer Surface Protein A - (:unkn) unknown (My University, 2014)
Arthritis is a common symptom of Lyme disease, a debilitating condition resulting from infection with Borrelia burgdorferi. A protein found on the surface of B. burgdorferi, outer surface protein A (OspA), is known to elicit an inflammatory immune response involving T helper cells. T helper 17 (Th17) cells are associated with the inflammatory cytokines interleukin-17 (IL-17) and interleukin-23 (IL-23) and have been implicated in the development of Lyme arthritis. The objective of this thesis is to provide further characterization of the immune response to B. burgdorferi OspA. The central hypothesis of this thesis is: Vaccination with OspA will predispose mice to developing a Th17 cell response and IL-17-dependent hind paw swelling following stimulation with live spirochetes. This hypothesis was tested by pursuing the following specific aims: 1) Determine the ability of OspA to induce a Th17 response, and 2) Determine the ability of OspA to induce IL-17-dependent inflammation. Our hypothesis was partially supported by data collected in this study. In vitro incubations of B. burgdorferi-stimulated splenic cells from OspA-vaccinated mice with various Th17-associated cytokine antibodies demonstrated a strong development of Th17 cell activity, particularly in mice deficient in the anti-inflammatory cytokine interleukin-10 (IL-10). While OspA-vaccinated, B. burgdorferi-infected wild-type mice treated with anti-IL-17 antibodies exhibited less swelling than untreated controls, this was not observed among IL-10-deficient mice. Collectively, these results suggest that OspA may promote Th17 cell activity following B. burgdorferi exposure in a murine model.
Keywords: Borrelia Burgdorferi; IL-17; IL-23; Lyme; OspA; Th17